The Effect of Age and Workload on Work Posture toward Musculoskeletal Disorders Complain on Loading and Unloading Workers - Russeng, Syamsiar S.; Saleh, Lalu Muhammad; Wahyulianti, Widya Nur; Palutturi, Sukri (Open Access Macedonian Journal of Medical Sciences, 2021)
Background: Workers in informal sector such as loading and unloading workers have a risk of experiencing health disorder of occupational disease such as musculoskeletloadingal disorders (MSDs). Such complain usually occurs on spine (back and neck) and upper limb. Most of the loading and unloading workers work using manual material handling, such as loading, unloading, pushing, pulling, throwing, moving, or rotating loads using their hands or other body parts. Such work method has musculoskeletal disorders (MSDs) risk, including low back pain. There are several factors causing the musculoskeletal disorders (MSDs) including individual factors (age and gender), work factors (workload and work posture), and work environment factors. Objective: The purpose of this study was to determine the direct and indirect effects of age and workload with work posture as an intervening variable against musculoskeletal disorders (MSDs) on loading and unloading workers at PT. Pelabuhan Indonesia IV (Persero) of Makassar Branch. Methods: The current research applied analytical observation with a Cross-Sectional approach involving 140 respondents selected through a simple random sampling technique. This research was further carried out at Pelabuhan Indonesia IV (Persero) of Makassar Branch in April-May 2021. Data obtained were analyzed using univariate, bivariate, and multivariate analysis. Results: There were 65 respondents (46.4%) who suffered from musculoskeletal disorder complaints in the high category followed by 53 respondents (37.9%) who suffered from musculoskeletal complaints in the very high category. It was also obtained that workload significantly affected the work position variable (p = 0.000 <0.05), age significantly affected the work posture variable (p = 0.000 <0.05), workload significantly affected the musculoskeletal disorders variable (p = 0.000 <0.05), and work posture significantly affected the musculoskeletal disorder variable (p = 0.000 <0.05). Conclusion: A significant indirect effect between workload and musculoskeletal disorders complaints through work posture variables. Significant indirect effect was also found between age and musculoskeletal disorder complaints through work posture. In addition, the highest category of low back pain complaints is in moderate disability.